THU0126 Multicenter retrospective study: Response to tocilizumab in clinical practice is not influenced by the number of previous biotherapy or by association with a DMARD. (23rd January 2014) - Pers, Y.-M.; Fortunet, C.; Constant, E.; Lambert, J.; Mazouyes, A.; Valnet, M.; Marotte, H.; Gaudin, P.; Wendling, D.; Maillefert, J.-F.; Jorgensen, C.
Abstract : Background: Tocilizumab (TCZ) is an effective treatment in rheumatoid arthritis (RA). The TCZ is indicated in failure of conventional DMARDs or after failure of first anti-TNF. Few factors are predictive of response to TCZ. We analyzed a cohort of patients in daily practice and identified predictors of response. Objectives: We conducted a retrospective study of 222 patients with RA treated by TCZ and followed by 5 academic reference centers in France. The main objective of the study was to identify clinical factors predictive of response to treatment with TCZ Methods: Clinical response was assessed by the disease activity score DAS28, taking into account the sedimentation rate. The efficacy of TCZ was evaluated at 12 and 24 weeks by the EULAR response criteria. Multivariate logistic regression was performed to study the association between EULAR response and the following baseline characteristics: gender, age, symptom duration, cigarette smoking habits, tender joints counts (TJC) and swollen joint counts (SJC), VAS global health, DAS28 score, concurrent prednisolone, combination therapy with DMARDs, and TCZ as the first biological therapy or after failure of at least one biological therapy. Results: Our cohort of 222 patients included 82% women with mean age of 55, 5 years and symptom duration of 15, 8 years. The mean baseline DAS28 was 5.14. 22, 8% of patients were active smokers. 71, 7% of patients had a positive rheumatoid factor and 66, 5% were anti-CCP antibodies positives. 80, 3% of patients were erosive. 65, 4% of patients take prednisolone. Methotrexate was associated with TCZ in 48% of patients and 13% were in other DMARDs. Only 14.8% of patients were naive to biologic agents. EULAR response was obtained in 68, 6% of patients at week 4, 77.2% of patients at week 12 and 86.7% of patients at week 24. In univariate analysis, an initial SJC>6 was associated with EULAR response at 4 weeks and 12 weeks (p<0.05). Active smoking was associated in univariate analysis with poorer EULAR response at 24 weeks. In multivariate analysis, an initial SJC>6 (OR 7.1 (1.05 to 48.08)) was significantly associated with EULAR response at 4 weeks (p<0.05). We did not find a better EULAR response in patients with combination DMARD and TCZ compared to TCZ monotherapy. Similarly, we did not find any difference in EULAR response between patients failing at least one biotherapy and those naive. Conclusions: In our cohort of 222 patients followed in "real life" during 24 weeks, we do not find any additive therapeutic effect of combination therapy with DMARD and TCZ compared to TCZ monotherapy. A SJC>6 is associated with better EULAR response at 4 weeks. Moreover, TCZ seems to be as efficient in the first line than after failure of biological therapy Disclosure of Interest: None Declared